Financial ratio analysis to asess the financial performance of PT.Indonesia Kendaraan Terminal Tbk - Swito, Agatha Aprilya; Wahyuningsih, Sulistya Dewi (Jurnal Mantik, 2025)
This research seeks to measure the financial ratio trends of PT. Indonesia Kendaraan Terminal Tbk from 2015 to 2023. The analysis employs a horizontal approach, which involves comparing the company's financial statements across different years and evaluating them through various financial ratios, such as liquidity, solvency, profitability, and activity ratios. The type of research used is quantitative descriptive research. The data used is secondary data sourced from the official website of the Indonesia Stock Exchange, www.idx.co.id, and primary data from the company's official website, www.indonesiacarterminal.co.id. The data collection methods used are documentation and literature study. Based on the research findings, the liquidity ratio indicates that the company is capable of meeting short-term obligations using current asset or available cash and cash equivalents. The solvency and profitability ratios saw a downturn during the COVID-19 pandemic but have since progressively improved, approaching their pre-pandemic levels. However, in general, both ratios still tend to indicate a declining performance. The activity ratio remains in a relatively good condition, despite the figures appearing relatively small.